Asie-Pacifique : une région politique en devenir (Note) - Cordonnier, Isabelle (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1994)
Without denying the importance of economies, the author underlines the necessity of analyzing the significance of Asia-Pacific as a political entity. The member States of the economics-oriented international organizations use the economic image of the region to gain political leverage at a regional or global level. This leads to an interrogation on the reality of « Asia-Pacific as a coherent political entity. The international relations in this area of the world also show an original pattern, insofar as the leadership of the « great powers » is questioned by « middle-sized » powers. The dialogue on collective security began recently and is a long way from achieving peace and stability in the region. It nevertheless shows the willingness of the Asia-Pacific States to overcome the difficulties of the post Cold War new world order